Application of artificial intelligence in medical care: review of current status - Pandya, Hetal; Pandya, Tanay (International Journal of Advances in Medicine, 2023)
Artificial intelligence (AI) has transformed almost all spheres of our life and has the potential to radically alter the field of health care. The increasing availability of healthcare data and rapid development of big data analytic methods has made possible the recent successful applications of AI in healthcare. Guided by relevant clinical questions, powerful AI techniques can unlock clinically relevant information hidden in the massive amount of data, which in turn can assist clinical decision making. To date, many AI systems have been developed in healthcare, but use and adoption in clinical practice has been limited. In this article, we tried to review few of promising AI techniques and tools, which can have a great impact on our health care system and in turn on quality of life.